О некоторых вопросах идентификации знаний в интеллектуальных системах - Булкин, В. И.; Шаронова, Наталья Валерьевна (Херсонський державний технічний університет, 2005)
In article questions of identification and the formal description of knowledge in information intellectual systems with use of the algebra-logic approach that allows by transition to switching circuits are considered to design means of processing and storage of knowledge as some intellectual processor of processing of knowledge.
Keywords: языки представления знаний; метрика семантическая; структурированность; процессор представления знаний